Using autogenous training as a health-saving technology for students - Kurkina, Larisa V.; Sidorova, Nadezhda A. (Физическое воспитание и студенческий спорт)
The article reveals factors leading to the deterioration of students’ health, examines the impact of health-saving technologies, and also provides a study of the effect of autogenic training on health and stress. Distribution of indicators of the health index of students of medical groups for the period of 2021–2023 is considered. Analysis of the study showed that the indicator M₁ (medical group – 1) tends to increase by 0.98 times. The M₂ indicator is 0.89 times, and the M₃ indicator is 0.61 times. In addition, there is the tendency of growth in all medical groups of students’ health, due to its control by the students themselves. To save the health of students, Department of Physical Education and Sports is developing a program for integrating physical education and autogenic training.